Impact of devascularization and tissue procurement on cell number and RNA integrity in prostatectomy tissue. Issue 16 (9th September 2015) - Payne Ondracek, Rochelle; Cheng, Jinrong; Gangavarapu, Kalyan J.; Azabdaftari, Gissou; Woltz, Jeff; Brese, Elizabeth; Omilian, Angela; Bshara, Wiam; Huss, Wendy J.; Mohler, James L.; Marshall, James R.
<x xml:space="preserve">Abstract</x> Background Minimizing the time between tissue devascularization in robot‐assisted laparoscopic radical prostatectomy (RALP) and tissue procurement should produce the highest quality tissue for research study. This study examines the relationship between intra‐operative time and two indicators of tissue integrity: number of epithelial cells per gram of tissue and RNA integrity numbers (RINs). The study also compares the RIN values of tissue obtained intra‐operatively by biopsy, before and after devascularization, to those from RALP specimen tissue, obtained through the routine research tissue procurement process. Methods Prostate tissues from two series of patients were analyzed. In the first, tissue from 18 patients undergoing RALP was analyzed for number of epithelial cells per gram of tissue. In the second, RIN values of tissue from 46 patients involved in a clinical study were analyzed. RIN values were assessed from RALP specimen tissue as well as tissue removed intra‐operatively by biopsy, before and after devascularization. Results Time from RALP to tissue procurement was not significantly associated with number of epithelial cells per gram of tissue or with RIN values. RINs of biopsy tissue obtained intra‐operatively before and after devascularization were similar. However, the RIN values of tissue from RALP specimens were significantly higher than those of biopsy tissue obtained either before or after devascularization. Conclusions Tissue quality, defined by number of epithelial cells or RIN values, was not affected by time between devascularization and procurement. Obtaining tissue from intra‐operative biopsies, either before or after devascularization, is not necessary and actually produced lower RINs than found in tissue from RALP specimens, obtained through the routine research tissue procurement process. Prostate 75:1910–1915, 2015. © 2015 Wiley Periodicals, Inc.